Proposta ergonômica para aprimoramento das condições de trabalho em unidades de alimentação e nutrição escolares - Zamin, Tatiane Vanessa (2023)
The study proposes suggestions for improving working conditions in School Food and Nutrition Units in the Santa Catarina region based on an analysis of the built environment. Kitchen spaces in UANEs must be functional, with adequate ergonomic conditions, to guarantee the comfort and well-being of all users who use these environments. The research procedures were divided into stages based on the Ergonomic Methodology for the Built Environment - MEAC (Villarouco, 2009, 2011). The first stage developed was the characterization of the research to approach the topic and select school units; the second stage was the photographic survey, using the Observation Tool in the environments and filling out the Environmental Inventory Form to evaluate the built environment. Then, in the third stage, semi-structured interviews were applied, and the RULA Method Tool was used for user evaluation. In the fourth stage, the method was based on the Poem of Desires to analyze and evaluate the environment by the user. Finally, the relevant literature was identified to develop improvements in the environments studied. Thus, it was found that for an ergonomic proposal to improve working conditions in UANEs, these points must be considered: lighting, ventilation, and adequate temperatures; organized spaces that facilitate the flow of employees; investment in efficient utensils and equipment; in addition to adaptable furniture for users, which can optimize the work process and reduce physical effort, which is essential to provide an adequate, safe and ergonomic environment.